Pedagogical aspects in the scientific activity of Immanuel Kant (Pedagogy of Higher and Secondary Education, 2012)
Havryshchak I. I. Pedagogical aspects in the scientific activity of Immanuel KantThe article investigates pedagogical activity of a famous German philosopher I. Kant, special attention is paid to the treatise «On Pedagogy». The conceptual provisions of the pedagogical foundations of the work were singled out; the analysis of teaching of the German philosopher was made.
Keywords: Immanuel Kant; the University of Knigsberg; pedagogical activity; pedagogical anthropology; education of the individual